Direct seending: Encompassing Principles of Conservation Agriculture - Chacón, Kattia (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Identifies initiatives within direct seeding, focused on conservation, identifying countries where this method has important implementations in grain production and food security support, supporting the preservation of natural resources and the implementation of a new paradigm in agriculture. agriculture without tillage and with healthier ecosystems.